2017
DOI: 10.1016/j.jaci.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution metabolomics to identify urine biomarkers in corticosteroid-resistant asthmatic children

Abstract: High-resolution metabolomics is a promising approach in asthma research. Five candidate markers were identified to be related to CS-resistant children with severe asthma. These compounds, upon validation, may contribute further in the understanding of CS resistance among children with severe asthma through the use of urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Metabolomics has also helped to establish candidate biomarkers for asthma severity and steroid resistance [94]. However, additional studies are needed to standardize the approach to metabolomics in asthma.…”
Section: Rna Transcriptomics (Study Of Gene Expression)mentioning
confidence: 99%
“…Metabolomics has also helped to establish candidate biomarkers for asthma severity and steroid resistance [94]. However, additional studies are needed to standardize the approach to metabolomics in asthma.…”
Section: Rna Transcriptomics (Study Of Gene Expression)mentioning
confidence: 99%
“…Biomarkers can be used to diagnose and understand disease pathophysiology. Previous studies confirmed numerous metabolite‐specific pathways related to immune responses and oxidative stress, and dysfunctional carbohydrate, amino acid, bile acid, steroid, nucleotide and lipid metabolism related to asthma . Inflammation and aberrant immune responses are characteristic features of all asthmatic phenotypes.…”
Section: Discussionmentioning
confidence: 65%
“…To date, no study has confirmed the precise value of single biomarker approaches, such as using F E NO or peripheral blood eosinophilia, to diagnose childhood asthma. Because any single biomarker for asthma may lack sensitivity, specificity, stability and manoeuvrability, various indicators including combinations of metabolites have been increasingly assessed for diagnosing asthma and its subtypes . A previous study demonstrated that PLS‐DA model on nuclear magnetic resonance data distinguished asthma and its subtypes with >90% accuracy .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics studies comparing asthmatics and healthy controls are useful to identify altered metabolic pathways and to expand our knowledge about the disease pathophysiology. Metabolomics can be also useful for clinical practice, such as evaluating consequences and the effect of a specific treatment or giving insights about altered pathways in treatment-resistant subjects and encourage the development of new target therapies (18,19,22,(31)(32)(33)(34). Metabolomics can also be used to differentiate asthma among other airway diseases, such as chronic obstructive pulmonary disease (35).…”
Section: Research and Clinical Valuementioning
confidence: 99%